Clinopodium kewensis (Lamiaceae): a new species from India - Chandra, Rimjhim; Güner, Özal; Çeti̇n, Özlem (Phytotaxa, 2025)
Clinopodium species show high morphological diversity, and their main diagnostic characteristics are calyx and corolla length, verticillaster arrangement, bract, nutlet shape and size and their rootlet. This manuscript describes and provides detailed morphological and molecular information about a new species, Clinopodium kewensis R.Chandra & Ö.Güner, and its close relatives. The new species resembles Clinopodium gracile complex, but is distinguished by its densely retrorse white pubescent stem, calyx teeth shape, corolla tube, fewer flowers in verticillasters, linear bract, and ellipsoid nutlet. In addition, nrITS DNA region sequences were used to find the relationships of the new species to its close relatives and determine its correct phylogenetic position within the outgroup species belonging to the genera Mentha, Micromeria, Origanum, Satureja, Ziziphora, Thymbra, and Thymus. The presently examined Clinopodium kewensis is the fifth addition of Clinopodium species to the flora of Himachal Pradesh and the sixth addition to the flora of India.